Information content of dividend changes in an emerging market - Abdullah, Nur Adiana Hiau; Abdul Rashid, Rosemaliza; Ibrahim, Yusnidah (Bond University, 2004)
Supports on the free cash flow and agency cost theory from dividend annoucement studies have been heavily discussed in the western literature, but they have not been given much attention in the Asian countries, particularly Malaysia.This paper focuses on examining the relationship of the stock market reactions due to dividend announcements and ten company-specific variables identified from the literature as potential determinants.The results from cross-sectional and stepwise regressions both showed that none of the determining variables could explain the variation in cumulative abnormal returns (CARs) for the increasing dividend announcements. For decreasing dividend announcements, both regressions identified the degree of anticipation to be significant and inversely related to CARs.In addition, the indigenous population ownership, which is a unique characteristic of the Malaysian equity market is also found to be significant in influencing the effect of decreasing dividend announcements. The findings provide no support for the free cash flow and agency cost theory.